2x+1+3x-4-4x=2x+4-3+1x

Simple and best practice solution for 2x+1+3x-4-4x=2x+4-3+1x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+1+3x-4-4x=2x+4-3+1x equation:



2x+1+3x-4-4x=2x+4-3+1x
We move all terms to the left:
2x+1+3x-4-4x-(2x+4-3+1x)=0
We add all the numbers together, and all the variables
2x+3x-4x-(3x+1)+1-4=0
We add all the numbers together, and all the variables
x-(3x+1)-3=0
We get rid of parentheses
x-3x-1-3=0
We add all the numbers together, and all the variables
-2x-4=0
We move all terms containing x to the left, all other terms to the right
-2x=4
x=4/-2
x=-2

See similar equations:

| 9^2x=66 | | 6^2x-6^x=-2 | | 1+10m=-17+8m | | 6=2.35714285x | | 3/4(2x-8)=4x+2 | | 6=2.3x | | 4x-3=+12x+5 | | (3x-10)/2=x | | y-3/8=14 | | 14+5n=4n+4 | | 15=60+15g | | w÷3+4=8 | | 100t-9=0 | | 3/4(2x-8)=4x-2 | | 3(2x-8)=4x-2 | | 5p+3p-7=1+10p | | X+95=3x-27 | | 10x+20-5x=3x+40+6-2x | | -6=m/2-4 | | 9*2^(9x)=52.9 | | 4x^-3x-5=0 | | -6=x/8-10 | | -2k-6=-5-k+1+1 | | (2*x)*6=(11*x)-9/2 | | 4-1/3n=-20 | | 2x^2-16=14 | | 4-1/3n=20 | | 13=x/5+7 | | (16x+12)°+(14x+28)°=180° | | 2x^-16=14 | | u/3=84 | | 6+x/4=9 |

Equations solver categories